Effect of Temperature and Chain Length on the Acoustic Behavior of Ammonium Soaps in Methanol - Varma, R.P.; Kumar, Surendra (Asian Journal of Chemistry, 2010)
Ultrasonic velocities of ammonum soaps i.e. laurate, myristate, palmitate and stearate have been measured, in methanol at temperatures 308-323 K. Acoustic parameters such as: adiabatic compressibility, molar sound velocity, molar sound compressibility, intermolecular free length, relative association constant, specific acoustic impedance, solvation number and apparent molar compressibility have been evaluated in order to determine the micellar aggregation of these soaps. The effects of temperature and chain length on these parameters have been discussed.